A FUNDAMENTAL IDEA OF UNDERSTANDING A SENTENCE GRAMATICALLY - Sadiq, Nizamuddin (English Education Department, Universitas Islam Indonesia, 2010)
To study of syntax, the concept of structure is fundamental. However structure itself is a very general concept and most of the language learners are assumed that their understanding about sentence is obvious. For many people, a sentence is considered group of words. This idea is not appropriate when a deep study of fundamental idea of a sentence is done.Linguistically speaking, sentences are not formed by words alone but by structural units known as constituents. The constituent has a certain specifiable function in the structure of the thing as a whole. However, the. fundamental idea of a sentence grammatically is that a sentence consists of phrase. Therefore, sentence (S) consists of noun phrase (NP) and verb phrase (VP). The idea of phrase here is to accommodate even a single constituent A at a sentence has. The basic principle of sentence, therefore, is S=NP+VP. It is obvious that NP and VP directly form a sentence. Furthermore, in terms of relation that the phrase may have in a sentence, there are four kinds of phrase relation in a sentence. They are modification, complementation, predication, and coordination.